The cortisol awakening response and resilience in elite swimmers - Meggs, J.; Golby, J.; Mallett, C. J.; Gucciardi, D. F.; Polman, R. C. J. (International Journal of Sports Medicine, 2016)
The sports environment is stress-eliciting in that it encapsulates perceived uncontrollability, unpredictability and requires ego-involvement. The HPA axis has been shown (indicated by cortisol release) to respond to anticipated sports competition up to a week prior to the event. Research also alludes to the importance of individual differences, such as optimism and trait perfectionism, in moderating the impact of cortisol upon performance. In total, 41 (male n=27) national (n=38) and international (n=3) swimmers were recruited from northeast England and Australia. Swimmers completed a measure of resilience and also provided buccal saliva swabs, from which total cortisol release prior to and during the event was calculated. Findings revealed that resilience significantly predicted performance and the influence of AUC (cortisol release) upon performance was moderated by resilience. These findings suggest that resilience can influence athletic performance either directly or indirectly, through appraisal (i. e., interpretation of the stressor to be facilitative and non-threatening).